Multi-dimensional Vibration Reduction Analysis of Construction Vehicle Seat with 3-RPS Mechanism Under Different Installation Position - Yan Bijuan; Liang Huijun; Li Zhanlong; Zhang Wenjun (Jixie chuandong)
The construction vehicles runs and works on the off-road for a long time， and it is easy to produce violent vibration in many directions. To solve this problem， a 3-RPS parallel seat mechanism is proposed based on the comparative analysis of multiple parallel mechanisms. The single-open-chain theory and UG simulation are used to verify its "one flat and two turns" motion state. And the D-H matrix is used to analyze the positive pose model of seat mechanism motion. The seat mechanism model is established in Adams software， and the vibration damping performance of the seat model is simulated and analyzed for four different installation positions because of considering the different installation positions of the branch chain will produce different vibration damping effects. The research shows that the seat mechanism has good vibration damping performance. Branch chain is installed on the axis， the direction of vibration reduction effect is superior to the other position， and 120° three branches chain installed uniform damping effect is better than other ways. The results of this study can provide reference for the installation of parallel seats in construction vehicles under different working environments. At the same time， it is of great significance to improve the comfort and safety of construction vehicles.